Current Research Status and Application of Polymer/Carbon Nanofiller Buckypaper: A Review. Issue 16 (2nd November 2017) - Kausar, Ayesha; Ilyas, Hafsa; Siddiq, Muhammad
ABSTRACT: With recent development in the field of polymer-based composite paper, buckypaper technology has gained considerable research attention. Conventionally, polymeric composites have been fabricated using carbon nanofiller (carbon nanotube, graphene, and graphene oxide) reinforcement in polymer matrix. In buckypaper technology, freestanding thin porous nanofiller network is formed using various papermaking techniques, which may further improve physical properties of polymer/carbon nanofiller buckypaper composite. This review also aims to report technical aspects of polymer/carbon nanotube, polymer/graphene, and polymer/graphene oxide-based composite paper. Special emphasis is given to the application of polymer/carbon nanofiller buckypaper in fuel cell, batteries, sensor, artificial muscles, fire retardant materials, and liquid crystal cells. GRAPHICAL ABSTRACT: